Effects of Polyphenols in Aging and Neurodegeneration Associated with Oxidative Stress - Nova-Baeza, P (Bentham Science Publishers, 2022)
Aging is defined as the functional loss of tissues and organs over time. This is a biological, irreversible, progressive, and universal process that results from genetic and environmental factors, such as diet, physical activity, smoking, harmful alcohol consumption, and exposure to toxins, among others. Aging is a consequence of molecular and cellular damage built up over time. This damage begins with a gradual decrease in physical and mental capacity, thus increasing the risk of neurodegenerative diseases such as Alz-heimer’s and Parkinson’s disease. Neuronal, functional, and structural damage can be explained by an imbalance among free radicals, reactive oxygen species, reactive nitrogen species, and antioxidants, which finally lead to oxidative stress. Due to the key role of free radicals, reactive oxygen species, and reactive nitrogen species, antioxidant therapy may reduce the oxidative damage associated with neurodegeneration. Exogenous antioxidants are molecules that may help maintain the balance between the formation and elimination of free radicals, thus protecting the cell from their toxicity. Among them, polyphenols are a broad group of secondary plant metabolites with potent antioxidant properties. Here, we review several studies that show the potential role of polyphenol consumption to prevent, or slow down, harmful oxidative processes linked to neurodegenerative disorders. © 2022 Bentham Science Publishers.